2021
DOI: 10.5194/egusphere-egu21-5089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the Bubble Trap Feeding Eruptions of Strokkur Geyser, Iceland

Abstract: <p>Geysers are characterized by regular eruptions of hot water fountains. Their internal system consists of a heat source at depth, an often complex crack system and a conduit linking it to the surface. The conduit and crack system is filled with water, steam and gases similar to a volcano. Bubble traps are sometimes and rarely mapped and alternative heat-driven models for geyser eruptions exist.</p><p>Using a multidisciplinary, dense and close network of video cameras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We used seismic data recorded at 5–14 m distance south and east of the pool of Strokkur geyser, Iceland (Eibl, Walter, et al., 2020). The sensors are Nanometrics Trillium Compact Posthole 20 s seismometers at locations S2, S3, S5 and Nanometrics Trillium Compact 120 s at locations S1, S4 (see Figure 1b) in the 7L seismic network (Eibl, Walter, et al., 2020). The seismometers were installed on 10 June 2018 for 4.5–5.25 hr and recorded at a sampling rate of 400 Hz.…”
Section: Overview Of Instrument Network Near Strokkur and Eruption Be...mentioning
confidence: 99%
“…We used seismic data recorded at 5–14 m distance south and east of the pool of Strokkur geyser, Iceland (Eibl, Walter, et al., 2020). The sensors are Nanometrics Trillium Compact Posthole 20 s seismometers at locations S2, S3, S5 and Nanometrics Trillium Compact 120 s at locations S1, S4 (see Figure 1b) in the 7L seismic network (Eibl, Walter, et al., 2020). The seismometers were installed on 10 June 2018 for 4.5–5.25 hr and recorded at a sampling rate of 400 Hz.…”
Section: Overview Of Instrument Network Near Strokkur and Eruption Be...mentioning
confidence: 99%
“…The elevation of West Crater is 1233 m, and the boiling point of pure water at this elevation is approximately 96°C. Previous studies of geysers have reported that water temperature rises at the time of geyser eruption (e.g., Nishimura et al, 2006;Eibl et al, 2021).…”
Section: − 2 Thermometermentioning
confidence: 99%
“…The seismic signals recorded at Old Faithful geyser in Yellowstone National Park, which has a vent opening of approximately 2 m × 1 m, are generated by bubble activity (growing, collapsing, or moving of bubbles) in boiling uid in the geyser conduit (Kieffer, 1984;Kedar et al, 1996;Kedar and Kanamori, 1998). Eibl et al (2021) reported that seismic tremors at Old Faithful are clustered in two dominant source locations: a deeper location (approximately 23.7 m depth) representing a sealed bubble reservoir, and a shallower location (approximately 5 m depth) representing the conduit.…”
Section: -4 Seismometermentioning
confidence: 99%
See 1 more Smart Citation